Pengaruh Penggunaan Lapis Tipis Beton Aspal pada Lajur Tanjakan Preservasi Jalan: (Studi Kasus: Aceh Tengah - Nagan Raya - Lhok Seumot - Jeuram) - Ramadhana, M. Ramadhana; Zakia, Zakia; Febrianti, Dian (Tameh, 2022)
Asphalt, also known as bitumen, is a mixture of binders used as road preservation. On the BTS road preservation project package. Central Aceh/Nagan Raya – Lhok Seumot – Jeuram (MYC) uses a thin layer of Asphalt Concrete as a treatment for road damage. Asphalt concrete thin layer is a hot asphalt mixture that can be used as a surface layer on road pavement which functions as a road preservation layer. The problem raised and also a research is how the feasibility of a thin layer of asphalt concrete on an incline. The method used in this study is based on testing Job Mix Asphalt, Traffic Counting, and direct observation of asphalt work in the field as well as supporting data in the form of information from consultants or contractors. Asphalt concrete thin layers cannot be used on incline lanes because the asphalt road contains a very fine aggregate mixture. Comparison of thin layers of asphalt concrete with AC – BC using the Traffic Counting method explains that vehicles passing on roads using thin layers of asphalt concrete on the dominant incline lane are more vehicles unable to climb compared to vehicles passing on roads using asphalt AC – BC. The use of a thin layer of asphalt concrete cannot be used for incline lanes, but a thin layer of asphalt concrete is highly recommended for the use of asphalt roads in urban areas.